2021
DOI: 10.1002/jaba.838
|View full text |Cite
|
Sign up to set email alerts
|

Teaching comprehension of double‐meaning jokes to young children

Abstract: Various forms of humor are an important aspect of social interactions, even at an early age. Humor comprehension is a repertoire that is said to emerge between the ages of 7 and 11 years, and this is primarily attributed to a child's level of cognitive development. The behavioral literature has suggested that various forms of complex verbal behavior, including the use and comprehension of humor, are learned operants that can be taught using systematic teaching procedures. The current study used multiple exempl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…The results of the present study confirmed the second hypothesis regarding a link between metacognitive knowledge and ability to grasp mathematical jokes in both groups of participants: greater metacognitive knowledge was associated with better understanding of mathematical jokes and poorer metacognitive knowledge was associated with poorer understanding of mathematical jokes. This is in line with Jackson et al (2021) who claim that incorporating jokes in teaching helps students' cognitive development. Reilly (2006) argues that humor as a communicative process in the context of learning can spark creativity and expand the range of possibilities that students entertain.…”
Section: Association Between Metacognitive Knowledge and Understandin...supporting
confidence: 89%
See 1 more Smart Citation
“…The results of the present study confirmed the second hypothesis regarding a link between metacognitive knowledge and ability to grasp mathematical jokes in both groups of participants: greater metacognitive knowledge was associated with better understanding of mathematical jokes and poorer metacognitive knowledge was associated with poorer understanding of mathematical jokes. This is in line with Jackson et al (2021) who claim that incorporating jokes in teaching helps students' cognitive development. Reilly (2006) argues that humor as a communicative process in the context of learning can spark creativity and expand the range of possibilities that students entertain.…”
Section: Association Between Metacognitive Knowledge and Understandin...supporting
confidence: 89%
“…Unlike the Olugbemiro study, which recruited college students, the present study tested middle school children with learning disabilities. Integrating jokes in class is considered an important aspect of social interaction even at young ages, and an aid to cognitive development: Using diverse forms of complex verbal formulations, including jokes, helps to develop cognitive abilities, increases metacognitive knowledge, and fosters an internal locus of control (Jackson et al, 2021;Tonkovich, 2020). This is the core of the present study, which examined the links and the differences in metacognitive knowledge, locus of control, and understanding of mathematical jokes between students with and without learning disabilities.…”
Section: Metacognitive Knowledge Locus Of Control and Mathematical Jo...mentioning
confidence: 99%
“…There were no significant differences between phonological and lexical humor in children with articulation disorders although they had more dif f iculties with understanding r iddles (Abrahamsen, 2004). They have deficits in comprehension of double-meaning jokes but can be successfully taught using systematic teaching procedures to improve humor appreciation and comprehension (Jackson et al 2021). Can these children distinguish lies or deception from joking?…”
Section: Disability Art Cinema Media and Literaturementioning
confidence: 95%
“…Humor is defined as the faculty of perceiving and expressing or appreciating what is amusing or comical (Stein, 1980) and is universal (Jiang et al, 2019). Humor is important not only for adults as a social tool but also as a crucial part of children's learning, development, and social interactions (Krogh, 1985;McGhee, 2019;Recchia and Loizou, 2019;Jackson et al, 2021). McGhee's (1979) cognitive-stage theory is the most recognized reference for understanding humor development, reflecting four specific development phases tightly connected to children's cognitive development.…”
Section: Introductionmentioning
confidence: 99%